Rancang Bangun Receiver Sinyal ADS-B Pesawat Menggunakan RTL-SDR serta Antena 1090 MHz - Fery Irawan; Ciksadan Ciksadan; Suroso Suroso (Program Studi Teknik Elektro Universitas Khairun, 2020)
Automatic Dependent Surveillance Broadcast (ADS-B) is a surveillance technology used in air navigation. This technology can view information in the form of 24 bit ICAO aircraft addresses, ident or squawk, latitude, altitude, nationality, speed, longitude, track and heading. The current development problem can only be done with the Flight Radar24 web-based application, so it requires an internet connection to operate. To solve this problem, the necessary hardware is needed that can receive ADS-B signal with a frequency of 1090MHz and can translate it into information. The RTL-SDR R820T2 is a software-based hardware device that can receive a wide range of signals from 25 MHz - 1700MHz. To maximize signal reception, an additional omnidirectional antenna is capable of receiving signals from all directions. With this system, it is expected to make it easier to fly directly without an internet connection.